Keepers of the covenant - Austin, Lynn N. (Austin, Lynn N. Restoration chronicles, 2014)
"In a story drawn from the Old Testament books of Ezra and Nehemiah, Ezra, a Jewish scholar, is called upon to deliver his exiled people from Babylon to Jerusalem -- but the fight to keep God's Law is never easy"--